Understanding Pregnant Women with Opioid Use Disorder - Stiffler, Deborah; Amundson, Mia; Hapke, Lauren; Harvey, Emilie; Sizemore, Samantha; Smith, Savannah (Journal of Maternal and Child Health, 2019)
Background: Pregnant women with opioid use disorder are a major concern to the healthcare industry. They are not only one of the most stigmatized groups but are in need of outreach. Women who are afflicted by opioid addiction are a highly vulnerable group who are at risk of adverse pregnancy outcomes and perinatal complications. The purpose of this study was to do a meta-synthesis of the literature to gain a better understanding of the women